Land Suitability for Pitahaya (Hylocereus megalanthus) Cultivation in Amazonas, Perú: Integrated Use of GIS, RS, F-AHP, and PROMETHEE - Katerin M. Tuesta-Trauco; Rolando Salas López; Elgar Barboza; Jhon A. Zabaleta-Santisteban; Angel J. Medina-Medina; Abner S. Rivera-Fernandez; José A. Sánchez-Vega; Nerci M. Noriega-Salazar; Manuel Oliva-Cruz; Aqil Tariq; Jhonsy O. Silva-López (Remote Sensing)
Pitahaya (Hylocereus megalanthus), commonly known as dragon fruit, is grown in tropical areas and has a promising future in the world market. At present, it is a crop developed by small-scale farmers. However, finding optimal areas for installing this crop is a major challenge. In this study, we evaluated the suitability of land for pitahaya cultivation in the department of Amazonas using integrated multi-criteria techniques such as geographic information systems (GISs) and remote sensing (RS). The analytic hierarchy process (AHP) method was used to select and rank the suitability criteria. The fuzzy-AHP (F-AHP) method was then applied to perform pairwise comparisons and determine the linguistic scaling of the requirements, and, using the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE), the requirements with the highest preference for land suitability were selected. The results reported that for pitahaya cultivation, the most important criterion was mean annual temperature (20.70%), followed by soil organic matter (11.8%), mean annual rainfall (9.50%), and proximity to roads (9.0%). The final suitability map indicated that 0.006% (2.39 km2) was very suitable, 4.60% (1661.97 km2) moderately suitable, 0.10% (34.65 km2) marginally suitable, and 95.30% (34,459.31 km2) of the study area was not suitable.